Characterization and comparative profiling of MicroRNAs in a sexual dimorphism insect, Eupolyphaga sinensis Walker. - Wei Wu; Qiuping Ren; Chengjun Li; Yanyun Wang; Ming Sang; Yi Zhang; Bin Li (PLoS ONE, 2013)
BACKGROUND: MicroRNAs are now recognized as key post-transcriptional regulators in animal ontogenesis and phenotypic diversity. Eupolyphaga sinensis Walker (Blattaria) is a sexually dimorphic insect, which is also an important source of material used in traditional Chinese medicine. The male E. sinensis have shorter lifecycles and go through fewer instars than the female. Furthermore, the males have forewings, while the females are totally wingless. RESULTS: We used the Illumina/Solexa deep sequencing technology to sequence small RNA libraries prepared from the fourth-instar larvae of male and female E. sinensis. 19,097,799 raw reads were yielded in total: 7,817,445 reads from the female library and 11,280,354 from the male, respectively. As a result, we identified 168 known miRNAs belonging to 55 families as well as 204 novel miRNAs. Moreover, 45 miRNAs showed significantly different expression between the female and the male fourth-instar larvae, and we validated 10 of them by Stem-loop qRT-PCR. Some of these differentially expressed miRNAs are related to metamorphosis, development and phenotypic diversity. CONCLUSIONS/SIGNIFICANCE: This is the first comprehensive description of miRNAs in E. sinensis. The results provide a useful resource for further in-depth study on molecular regulation and evolution of miRNAs. These findings not only enrich miRNAs for hemimetabolans but also lay the foundation for the study of post-transcriptional regulation on the phenomena of sexual dimorphism.